2022
DOI: 10.1002/vms3.970
|View full text |Cite
|
Sign up to set email alerts
|

Role of cervids in the epidemiology of bovine ephemeral fever virus infection in the Republic of Korea: A cross‐sectional retrospective study

Abstract: Background Bovine ephemeral fever (BEF) is a viral disease in cattle and buffaloes, with subclinical involvement in various ruminant species. Objectives This study aimed to investigate bovine ephemeral fever virus (BEFV) transmission in deer in the Republic of Korea (ROK) and the potential risk factors associated with seropositivity. Methods We conducted a retrospective cross‐sectional serological survey of neutralising antibodies against BEF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…By phylogenetic analysis based on the Glycoprotein gene, BEFV strains are divided into four clusters: Middle East, East Asia, South Africa, and Australia [ 88 ]. It has been suggested that cervid species may serve as important reservoirs for transmitting the disease [ 89 ], which manifests clinically by the sudden onset of fever, lameness, rigidity, and spontaneous recovery in three days [ 23 , 90 , 91 ].…”
Section: Bovine Ephemeral Fevermentioning
confidence: 99%
“…By phylogenetic analysis based on the Glycoprotein gene, BEFV strains are divided into four clusters: Middle East, East Asia, South Africa, and Australia [ 88 ]. It has been suggested that cervid species may serve as important reservoirs for transmitting the disease [ 89 ], which manifests clinically by the sudden onset of fever, lameness, rigidity, and spontaneous recovery in three days [ 23 , 90 , 91 ].…”
Section: Bovine Ephemeral Fevermentioning
confidence: 99%